Detrended fluctuation analysis detects altered coordination of running gait in athletes following a heavy period of training - Bellenger, C. R.; Arnold, J. B.; Buckley, J. D.; Thewlis, D.; Fuller, J. T. (Journal of Science and Medicine in Sport, 2019)
Objectives: To investigate whether functional overreaching affects locomotor system behaviour when running at fixed relative intensities and if any effects were associated with changes in running performance. Design: Prospective intervention study. Methods: Ten trained male runners completed three training blocks in a fixed order. Training consisted of one week of light training (baseline), two weeks of heavy training designed to induce functional overreaching, and ten days of light taper training designed to allow athletes to recover from, and adapt to, the heavy training. Locomotor behaviour, 5-km time trial performance, and subjective reports of training status (Daily Analysis of Life Demands for Athletes (DALDA) questionnaire) were assessed at the completion of each training block. Locomotor behaviour was assessed using detrended fluctuation analysis of stride intervals during running at speeds corresponding to 65% and 85% of maximum heart rate (HRmax) at baseline. Results: Time trial performance (effect size ±95% confidence interval (ES): 0.16 ± 0.06; p < 0.001), locomotor behaviour at 65% HRmax (ES: -1.12 ± 0.95; p = 0.026), and DALDA (ES: 2.55 ± 0.80; p < 0.001) were all detrimentally affected by the heavy training. Time trial performance improved relative to baseline after the taper (ES: -0.16 ± 0.10; p = 0.003) but locomotor behaviour at 65% HRmax (ES: -1.18 ± 1.17; p = 0.048) and DALDA (ES: 0.92 ± 0.90; p = 0.045) remained impaired. Conclusions: Locomotor behaviour during running at 65% HRmax was impaired by functional overreaching and remained impaired after a 10-day taper, despite improved running performance. Locomotor changes may increase injury risk and should be considered within athlete monitoring programs independently of performance changes. ABSTRACT FROM AUTHOR